Glass composition and composite powder material
Patent Information
- Application Number
- JP2021574675
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-28
- Filing Date
- 2021-01-20
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-01-20
AI Technical Summary
【0009】 本発明に係るガラス組成物からなるガラス粉末を含む複合粉末材料は、870℃といった低温度や870℃~900℃といった広い低温度域での均質な焼成が可能である。また、かかる複合粉末材料を焼成することで得られる焼成体は、高周波においても、低誘電率及び低誘電損失の実現が可能である。
Smart Images

Figure 0007632314000001 
Figure 0007632314000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass composition and a composite powder material comprising a powder of said glass composition. [Background technology]
[0002] Low-temperature co-fired ceramics (LTCC) are known, which are manufactured by stacking and firing sheets in which glass frit or a mixture of inorganic oxides (composite powder material) is dispersed in resin. For LTCC, the dielectric constant of the material itself must be reduced for various purposes, such as to reduce the thickness between layers to make it smaller, to reduce the distance between wiring to make it denser, and to improve functionality. Furthermore, materials with low dielectric loss, especially in the microwave region, are required to support the fifth generation communication standard (commonly known as 5G) in communication devices such as mobile phones and smartphones.
[0003] For example, Patent Document 1 discloses a mixture of alumina and borosilicate glass with a low content of alkali metal oxides, which is sintered at 950°C for two hours to achieve a dielectric constant of 5.7 or less and a dielectric loss of 0.0014 or less at high frequencies. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent No. 4047050 Summary of the Invention [Problem to be solved by the invention]
[0005] Metals with low electrical resistance such as gold, silver, and copper are used as electrode materials for LTCC, but silver electrodes are the most widely used. The firing temperature during the manufacture of LTCC is selected according to the thermal properties of the glass component contained in the composite powder material, such as the glass transition temperature Tg, softening point Ts, and crystallization temperature Tc, so that firing proceeds sufficiently, but is usually above 900°C. However, when the firing temperature exceeds 900°C, silver diffuses into the glass ceramics (fired body) and reduces the electrical properties of the material, or the periphery of the silver electrode turns brown due to oxidation and reduction. The diffusion of silver can be suppressed to some extent by lowering the firing temperature or shortening the firing time. However, with conventional materials, a dense fired body cannot be formed under the above-mentioned conditions, and the electrical properties are reduced. For this reason, there is a demand for a material that can be fired at a temperature of 900°C or less, more preferably at a temperature of about 870°C, and that can obtain the required electrical properties. On the other hand, when copper is used for the electrodes, diffusion into glass ceramics is unlikely to occur. However, when copper is oxidized during firing to become copper oxide, the electrical resistance increases and performance decreases. For this reason, firing in an oxygen-free reducing atmosphere is required. Firing in such a reducing atmosphere requires large-scale manufacturing equipment, making mass production difficult.
[0006] In Patent Document 1, low dielectric constant and low dielectric loss are achieved by firing at 950°C, but silver electrodes cannot be used at this firing temperature, and it is necessary to prepare large-scale manufacturing equipment and use copper electrodes, which increases the mass production cost.
[0007] The present invention has been made in view of the above, and aims to provide a glass composition for use in a composite powder material which can be fired at a low temperature so that silver electrodes can be used, and which can produce a fired body that can achieve a low dielectric constant and low dielectric loss at high frequencies. Specifically, the low-temperature sintering of composite powder materials refers to sintering at 870°C or uniform sintering in a wide low-temperature range such as 870°C to 900°C. The low dielectric constant refers to a dielectric constant of 6.5 or less. The low dielectric loss refers to a Q value, which is the reciprocal of the dielectric loss, of 500 or more when the measurement frequency is 1 MHz, and 450 or more when the measurement frequency is 14 GHz to 16 GHz. Another object of the present invention is to provide a composite powder material that contains the glass composition in powder form and has the above-mentioned properties. [Means for solving the problem]
[0008] As a result of extensive research, the inventors have discovered that by using a glass composition having a prescribed composition, firing at 900°C or less is possible and a low dielectric constant and low dielectric loss at high frequencies can be achieved, thereby completing the present invention. That is, the present invention is as follows. [1] Li 2 O and SiO in mole percent based on oxide 2 60% to 67%, B 2 O 3 20% to 29%, CaO 3% to 9%, and Al 2 O 3 3% to 6% and Li 2 O, Na 2 O, and K 2 Molar ratio of O content (Li 2 O:Na 2 OK 2 O) is 1:0-1.9:0-0.9. [2] Li 2 O, Na 2 O, and K 2 The glass composition according to the above [1], wherein the total content of O is 0.3% to 1.0% in mole percent based on the oxides. [3] The glass composition according to [1] or [2] above, having a shrinkage starting temperature of 790°C or higher. [4] The glass composition according to any one of the above [1] to [3], which has a softening point of 900° C. or lower. [5] Li2 The glass composition according to any one of the above [1] to [4], wherein the O content is 0.2% to 1.0% in mole % based on the oxide. [6] A composite powder material comprising 45% by mass to 55% by mass of glass powder and 45% by mass to 55% by mass of alumina filler, the glass powder being a powder made of the glass composition according to any one of [1] to [5] above. [7] The composite powder material according to [6], having a glass transition temperature of 650°C or higher. [8] The composite powder material according to [6] or [7], having a shrinkage starting temperature of 820°C or higher. [9] The composite powder material according to any one of [6] to [8] above, having a softening point of 900° C. or lower.
[10] The composite powder material according to any one of [6] to [9], wherein when the composite powder material is fired at 870°C for 20 minutes to obtain a fired body (A) and when the composite powder material is fired at 870°C for 60 minutes to obtain a fired body (B), the density expressed by {density of fired body (B) / density of fired body (A)}×100 is 98.0% to 102.0%.
[11] The composite powder material according to any one of [6] to
[10] above, wherein when the composite powder material is fired at 870°C for 60 minutes to obtain a fired body (B), and when the composite powder material is fired at 900°C for 60 minutes to obtain a fired body (C), the density expressed by {density of fired body (B) / density of fired body (C)}×100 is 99.0% to 101.0%. Effect of the Invention
[0009] A composite powder material containing glass powder made of the glass composition according to the present invention can be uniformly fired at a low temperature such as 870° C. or in a wide low temperature range such as 870° C. to 900° C. In addition, a fired body obtained by firing such a composite powder material can achieve low dielectric constant and low dielectric loss even at high frequencies. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to the embodiment described below.
[0011] [Glass composition] First, an embodiment of the glass composition of the present invention will be described. The glass composition of the present embodiment contains, in terms of mole percent based on oxides, SiO 2 60% to 67%, B 2 O 3 20% to 29%, CaO 3% to 9%, and Al 2 O 3 Contains 3% to 6% of Li 2 Contains O and Li 2 O, Na 2 O, and K 2 Molar ratio of O content (Li 2 O:Na 2 OK 2 O) is 1:0-1.9:0-0.9.
[0012] The glass composition of the glass composition of this embodiment will be described below. In this specification, the content of each component in the glass composition means the content in mole percent on an oxide basis unless otherwise specified.
[0013] SiO 2 is a component that stabilizes glass and is an essential component. From the viewpoints of stabilizing the glass and lowering the dielectric constant, the SiO 2 The content is 60% or more, preferably 62% or more, and more preferably 63% or more. On the other hand, in order to ensure the meltability of the glass and to enable the production of homogeneous glass at low cost, the SiO 2 The content is 67% or less, preferably 66.5% or less, and more preferably 66% or less.
[0014] B 2 O 3 is a component that promotes the firing of glass and is an essential component. In order to ensure sinterability at temperatures of 900° C. or less, the glass composition B of this embodiment is 2 O 3 The content is 20% or more, preferably 23% or more, and more preferably 24% or more. On the other hand, in order to prevent phase separation of the glass during melting, the B 2 O 3 The content of is 29% or less, preferably 27% or less, and more preferably 26% or less. Glass that is prone to phase separation is not suitable for stable mass production.
[0015] Al 2 O 3 is a component for stabilizing glass and is an essential component. In order to prevent phase separation of the glass, the Al of the glass composition of this embodiment 2 O 3 The content is 3% or more, preferably 3.5% or more, and more preferably 4% or more. On the other hand, in order to suppress the melting temperature of the glass from becoming high, the Al of the glass composition of this embodiment is 2 O 3 The content of is 6% or less, preferably 5.7% or less, and more preferably 5.5% or less. Glass with too high a melting temperature is not suitable for mass production.
[0016] CaO is an essential component which lowers the melting temperature of glass and also promotes firing. In order to ensure sinterability at temperatures of 900° C. or less, the CaO content of the glass composition of this embodiment is set to 3% or more, preferably 3.5% or more, and more preferably 4% or more. On the other hand, in order to reduce the dielectric constant, the CaO content in the glass composition of the present embodiment is set to 9% or less, preferably 7% or less, and more preferably 6% or less.
[0017] Li 2 O, Na 2 O and K 2 O is a component that promotes sintering and is useful for ensuring sintering at temperatures below 900°C. 2 O, Na2 O and K 2 O is also a component that tends to cause high dielectric loss at high frequencies. The inventors conducted repeated experiments and found that if the content ratio of these components satisfies certain conditions, the effect of promoting sintering can be obtained while the increase in dielectric loss can be suppressed. From the above findings, the Li of the glass composition of this embodiment 2 O, Na 2 O, and K 2 Molar ratio of O content (Li 2 O:Na 2 OK 2 O) should be 1:0~1.9:0~0.9. That is, the glass composition of the present embodiment is Li 2 O is contained as an essential component. 2 OK 2 O may or may not be contained.
[0018] In order to particularly suppress the increase in dielectric loss at high frequencies, the alkali metal oxide in the glass composition of this embodiment is Li 2 O only, Na 2 OK 2 It is most preferable that O is not contained. 2 OK 2 Even if it contains O, Li 2 O, Na 2 OK 2 Li 2 The O content is preferably 35% or more, more preferably 60% or more, and most preferably 80% or more.
[0019] In order to particularly suppress the increase in dielectric loss at high frequencies and to facilitate the manufacture of glass by lowering the softening point of the glass, the Li content in the glass composition of this embodiment is 2 O and Na 2 Molar ratio of O content (Li 2 O:Na 2 O) is 1:1.9 or less, more preferably 1:1.5 or less, and even more preferably 1:1.3 or less. 2O and Na 2 Molar ratio of O content (Li 2 O:Na 2 O) is preferably 1:0.6 or more, more preferably 1:0.75 or more, and most preferably 1:0.9 or more. 2 Na when it contains O 2 The O content is Li 2 The content of Na is 1.9 times or less, more preferably 1.5 times or less, and further preferably 1.3 times or less, of the content of O. 2 Na when it contains O 2 The O content is preferably 0.6 times or more, more preferably 0.75 times or more, and most preferably 0.9 times or more.
[0020] In order to particularly suppress the increase in dielectric loss at high frequencies, the Li in the glass composition of this embodiment is 2 O and K 2 Molar ratio of O content (Li 2 OK 2 O) is 1:0.9 or less, more preferably 1:0.7 or less, even more preferably 1:0.5 or less, and particularly preferably 1:0.3 or less. That is, K 2 K when containing O 2 The O content is Li 2 It is 0.9 times or less the O content, more preferably 0.7 times or less, further preferably 0.5 times or less, particularly preferably 0.3 times or less.
[0021] From the viewpoint of reducing dielectric loss at high frequencies, Na in the glass composition of this embodiment 2 O and K 2 Molar ratio of O content (Na 2 OK 2 O) is preferably 1:1 or less, more preferably 1:0.5 or less, even more preferably 1:0.3 or less, and particularly preferably 1:0.25 or less. 2 O may not be contained, but if it is contained, the molar ratio is preferably 1:0.1 or more. 2 The O content is Na 2The content is preferably 1 time or less of the O content, more preferably 0.5 time or less, further preferably 0.3 time or less, particularly preferably 0.25 time or less, and preferably 0.1 time or more.
[0022] From the viewpoint of improving sinterability, Li in the glass composition of this embodiment 2 O, Na 2 O, and K 2 The total content of O is preferably 0.3% or more, more preferably 0.4% or more, and further preferably 0.5% or more. On the other hand, in order to reduce the dielectric loss at high frequencies, the Li 2 O, Na 2 O, and K 2 The total content of O is preferably 1.0% or less, more preferably 0.9% or less, and further preferably 0.8% or less.
[0023] Among the above alkali metal oxides, Li 2 O is an essential component. 2 The content of O is preferably 0.2% or more, more preferably 0.3% or more, from the viewpoint of improving sinterability. 2 The O content is preferably 1.0% or less, more preferably 0.9% or less, and further preferably 0.8% or less.
[0024] BaO is a component that can replace CaO, and part or all of CaO can be replaced with BaO. BaO is a component that lowers the melting temperature of glass and promotes firing, and although it is not an essential component, it may be included in the glass composition of the present embodiment. In order to ensure sinterability at temperatures of 900°C or less, the content of BaO in the glass composition of the present embodiment is preferably 3% or more, more preferably 3.5% or more, and even more preferably 4% or more. On the other hand, in order to reduce the dielectric constant, the BaO content in the glass composition of the present embodiment is preferably 9% or less, more preferably 7% or less, and further preferably 6% or less.
[0025] SrO is a component that can replace CaO, and part or all of CaO can be replaced with SrO. SrO is a component that lowers the melting temperature of glass and promotes firing, and although it is not an essential component, it may be contained in the glass composition of the present embodiment. In order to ensure sinterability at temperatures of 900°C or less, the content of SrO in the glass composition of the present embodiment is preferably 3% or more, more preferably 3.5% or more, and even more preferably 4% or more. On the other hand, in order to reduce the dielectric constant, the SrO content in the glass composition of the present embodiment is preferably 9% or less, more preferably 7% or less, and further preferably 6% or less.
[0026] CaO, SrO and BaO may all be contained, or any one or two of them may be selected and used. The total content of these is preferably 3% or more, more preferably 3.5% or more, and even more preferably 4% or more. On the other hand, in order to reduce the dielectric constant, the content thereof is preferably 9% or less, more preferably 7% or less, and further preferably 6% or less.
[0027] The glass composition of the present embodiment may contain components other than those described above, so long as the content is within a range that provides the effects of the present invention. For example, the glass of the present embodiment may contain MgO, ZnO, CeO 2 , ZrO 2 , CuO, and AgO. Note that these are merely examples, and other components that may be contained in the glass composition of the present embodiment are not limited to these. The total content of other components that may be contained is preferably 5% or less, and more preferably 3% or less.
[0028] The appropriate temperature for firing the composite powder material containing the glass powder made of the glass composition of this embodiment depends on the shrinkage start temperature Sp and softening point Ts of the glass composition. The shrinkage start temperature Sp is the temperature at which the melting shrinkage of the glass composition begins to occur, and is the temperature at which the third inflection point is shown in differential thermal analysis (DTA).
[0029] If the shrinkage start temperature Sp of the glass composition of this embodiment is too low, even if the temperature is suitable for firing the composite powder material containing the glass composition, the resin component used for forming a slurry when firing the composite powder material will not be decomposed and will remain in the fired body as it is or as a carbon component, which may hinder the formation of a dense fired body. Therefore, the shrinkage start temperature Sp of the glass composition is preferably 750°C or higher, more preferably 770°C or higher, and even more preferably 790°C or higher. In addition, the shrinkage start temperature Sp of the glass composition is preferably 850°C or lower, more preferably 840°C or lower, and even more preferably 830°C or lower, from the viewpoint of lowering the firing temperature of the composite powder material.
[0030] From a similar viewpoint, the softening point Ts of the glass composition of this embodiment is preferably 850° C. or higher, more preferably 860° C. or higher, and even more preferably 870° C. or higher. The softening point Ts of the glass composition of this embodiment is preferably 920° C. or lower, more preferably 910° C. or lower, and even more preferably 900° C. or lower.
[0031] The method for producing the glass composition of the present embodiment is not particularly limited, but examples thereof include the following method.
[0032] First, the raw materials are mixed to prepare a raw material mixture. The raw materials are not particularly limited as long as they are raw materials used in the manufacture of ordinary oxide-based glasses, and oxides, carbonates, etc. can be used. The raw material mixture is prepared by appropriately adjusting the types and ratios of the raw materials so that the composition of the resulting glass falls within the above-mentioned range.
[0033] Next, the raw material mixture is heated by a known method to obtain a melt. The heating temperature (melting temperature) is preferably 1500° C. or higher, more preferably 1550° C. or higher, and preferably 1700° C. or lower, more preferably 1650° C. or lower. The heating time is preferably 90 minutes or longer, more preferably 100 minutes or longer, and preferably 180 minutes or lower, more preferably 140 minutes or lower.
[0034] Thereafter, the molten material is cooled and solidified to obtain the glass composition of the present embodiment. The cooling method is not particularly limited. For example, the molten material can be cooled using a roll-out machine, a press machine, or the like, or can be rapidly cooled by dropping the molten material into a cooling liquid, or the like.
[0035] The glass composition of the present embodiment thus obtained may be in any form, such as a block, a plate, a thin plate (flake), or a powder.
[0036] [Composite powder material] Next, the composite powder material of this embodiment will be described. The composite powder material of this embodiment preferably contains 45% by mass to 55% by mass of glass powder made of the above glass composition, and 45% by mass to 55% by mass of alumina filler.
[0037] The glass powder contained in the composite powder material of the present embodiment is a glass powder made of the above-mentioned glass composition. In the composite powder material of this embodiment, by setting the glass powder content to 45 mass % or more, sufficient sinterability can be achieved at temperatures of 900° C. or less. Therefore, the glass powder content in the composite powder material of this embodiment is preferably 45 mass % or more, more preferably 47 mass % or more, and further preferably 48 mass % or more. On the other hand, in the composite powder material of this embodiment, by setting the glass powder content to 55 mass % or less, a sufficient amount of alumina filler described later can be contained, and a sufficiently low dielectric loss can be obtained at high frequencies. Therefore, the glass powder content in the composite powder material of this embodiment is preferably 55 mass % or less, more preferably 53 mass % or less, and further preferably 51 mass % or less.
[0038] The average particle size D50 of the glass powder in this embodiment is preferably 5 μm or less, more preferably 4 μm or less, and even more preferably 3 μm or less, from the viewpoint of obtaining a dense fired body by firing. On the other hand, glass powders with too small an average particle size D50 have high manufacturing costs when produced industrially. Therefore, the average particle size D50 of the glass powder in this embodiment is preferably 0.5 μm or more, more preferably 0.8 μm or more, and even more preferably 1.5 μm or more. In addition, the particle size at which the integrated amount is 50% cumulatively from the smallest particle in a volume-based cumulative particle size distribution curve measured by a laser diffraction method is defined as the "average particle size D50."
[0039] The alumina filler is a component that reduces dielectric loss at high frequencies. In the composite powder of this embodiment, the alumina filler content is 45 mass% or more, so that a sufficiently low dielectric loss can be obtained at high frequencies. Therefore, the alumina filler content in the composite powder material of this embodiment is preferably 45 mass% or more, more preferably 47 mass% or more, and even more preferably 49 mass% or more. Meanwhile, in the composite powder material of this embodiment, by setting the alumina filler content to 55 mass % or less, sufficient sinterability can be achieved at temperatures of 900° C. or less. Therefore, the alumina filler content in the composite powder material of this embodiment is preferably 55 mass % or less, more preferably 53 mass % or less, and further preferably 52 mass % or less.
[0040] In this embodiment, the average particle size D50 of the alumina filler is preferably 5 μm or less, more preferably 4 μm or less, and even more preferably 3 μm or less, in order to obtain a sufficiently dense sintered body by sintering, to improve the surface smoothness of the obtained sintered body, and to further reduce the dielectric loss at high frequencies. On the other hand, in order to improve the bending strength, the average particle size D50 of the alumina filler in this embodiment is preferably 0.3 μm or more, more preferably 0.6 μm or more, and even more preferably 1.5 μm or more.
[0041] The purity of the alumina filler of this embodiment is preferably as high as possible. 2 O 3The content is preferably 99.5% by mass or more, more preferably 99.9% by mass or more, and even more preferably 99.99% by mass or more.
[0042] In addition, Al in the alumina filler 2 O 3 Although alumina may have a plurality of crystal structures, from the viewpoint of reducing dielectric loss, the alumina filler in this embodiment preferably contains a large amount of corundum crystals. In the alumina filler in this embodiment, the proportion of corundum crystals is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 75% by mass or more, and most preferably 100% by mass, based on the proportion of all crystal components. The ratio is determined by X-ray crystal structure analysis.
[0043] The composite powder material of the present embodiment may further contain an inorganic oxide filler other than the alumina filler, such as a magnesia filler. The magnesia filler is a component that has the effect of preventing the precipitation of orthoboric acid from the glass powder, which has low water resistance, after the composite powder material is made into a green sheet. If orthoboric acid is precipitated on the surface of the green sheet, poor adhesion occurs at the laminated interface after lamination and firing, resulting in problems such as peeling and cracking. In addition to the addition of magnesia filler, the precipitation of orthoboric acid can also be prevented by, for example, keeping the green sheet at a low temperature and low humidity, shortening the storage time, etc. Therefore, in the composite powder material of this embodiment, the magnesia filler is not an essential component.
[0044] When it is desired to obtain the effect of preventing the precipitation of orthoboric acid by adding magnesia filler, the content of the magnesia filler is preferably 0.3 mass % or more, more preferably 0.5 mass % or more, and further preferably 0.8 mass % or more. On the other hand, if the content of the magnesia filler is too high, there is a risk that the sintering property will be insufficient at temperatures of 900° C. or less. Therefore, the content of the magnesia filler in the composite powder material of this embodiment is preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 1.5% by mass or less.
[0045] Examples of inorganic oxide fillers other than alumina fillers include magnesia fillers, as well as steatite, forsterite, cordierite, willemite, fused quartz, cerium oxide, zirconium oxide, copper oxide, and silver oxide.
[0046] The composite powder material of the present embodiment may contain other components than those described above, as long as the content is within the range in which the effects of the present invention are achieved. For example, the composite powder material of the present embodiment may contain glass frit, lithium carbonate, sodium carbonate, potassium carbonate, calcium carbonate, barium carbonate, strontium carbonate, boric anhydride, aluminum hydroxide, etc., which act as a sintering aid. Note that the glass frit acts as a sintering aid and is therefore different from the glass powder made of the glass composition of the present embodiment. The other components described above are merely examples, and the other components that the composite powder material of the present embodiment may contain are not limited to these.
[0047] The composite powder material of the present embodiment is obtained by mixing glass powder made of the above glass composition, an alumina filler, and other components added as necessary. The mixing method is not particularly limited, and a known mixing method can be adopted. The preferred aspects of the glass composition constituting the glass powder are the same as the preferred aspects of the above glass composition.
[0048] The composite powder material of the present embodiment is preferably used to obtain a sintered body such as LTCC by sintering. The sintering method is not particularly limited, but may be, for example, a green sheet method. The green sheet method will be briefly described below.
[0049] In the green sheet method, the composite powder material of this embodiment is first mixed with a resin. At this time, additives such as a plasticizer may be added as necessary. Next, it is mixed with a solvent to form a slurry, which is then formed into a sheet on a film such as polyethylene terephthalate. Finally, the slurry formed into a sheet is dried to remove the solvent, resulting in a green sheet.
[0050] The resin is not particularly limited, and any resin that is usually used in the green sheet method may be used, for example, polyvinyl butyral resin, acrylic resin, etc. The plasticizer is not particularly limited, and any plasticizer generally used in the green sheet method may be used. For example, dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate, etc. may be used. The solvent is not particularly limited, and any solvent that is usually used in the green sheet method may be used, such as toluene, xylene, butanol, etc. The method for forming the slurry is not particularly limited, but may be, for example, a doctor blade method.
[0051] On the obtained green sheet, wiring patterns and vias serving as through conductors are formed as necessary by screen printing or the like using silver paste, silver conductor, etc. Also, an overcoat glass for protecting the wiring, etc. made of silver may be formed by screen printing or the like. Thereafter, a plurality of green sheets are laminated as necessary, cut into a desired shape, and fired to obtain a fired body (substrate).
[0052] In order to prevent deterioration of electrical properties due to diffusion of silver during firing and browning due to oxidation-reduction, the firing temperature is preferably 900° C. or less, more preferably 880° C. or less, and even more preferably 870° C. or less. Since the composite powder material of the present embodiment contains a predetermined amount of glass powder made of a glass composition with excellent sinterability, firing proceeds sufficiently even at such a low temperature. On the other hand, the firing temperature is preferably 850° C. or higher, more preferably 860° C. or higher, in order to allow the firing to proceed sufficiently. The time for firing the composite powder material of this embodiment is not particularly limited, but is, for example, about 20 minutes to 60 minutes.
[0053] The appropriate temperature for firing the composite powder material of this embodiment depends on the glass transition temperature Tg, the shrinkage onset temperature Sp, and the softening point Ts of the composite powder material. As described above, the shrinkage onset temperature Sp is the temperature at which the melting shrinkage of the glass composition begins to occur, and is the temperature at which the third inflection point is shown in differential thermal analysis (DTA). In addition, if the glass transition temperature Tg of the composite powder material of this embodiment is too low, even if the temperature is suitable for firing the composite powder material, the resin component used for forming the slurry during firing will not be decomposed and will remain in the fired body as it is or as a carbon component, which may hinder the formation of a dense fired body. Therefore, the glass transition temperature Tg of the composite powder material of this embodiment is preferably 650°C or higher, more preferably 665°C or higher, and even more preferably 680°C or higher. In addition, the glass transition temperature Tg of the composite powder material of this embodiment is preferably 730°C or lower, more preferably 715°C or lower, and even more preferably 710°C or lower, from the viewpoint of lowering the firing temperature of the composite powder material.
[0054] From the same viewpoint, the shrinkage start temperature Sp of the composite powder material of this embodiment is preferably 820° C. or more, more preferably 830° C. or more, and even more preferably 840° C. or more. The shrinkage start temperature Sp of the composite powder material of this embodiment is preferably 880° C. or less, more preferably 870° C. or less, and even more preferably 860° C. or less.
[0055] From the same viewpoint, the softening point Ts of the composite powder material of the present embodiment is preferably 865° C. or higher, more preferably 870° C. or higher, and even more preferably 875° C. or higher. The softening point Ts of the composite powder material of the present embodiment is preferably 910° C. or lower, more preferably 905° C. or lower, and even more preferably 900° C. or lower.
[0056] When firing the composite powder material of this embodiment, multiple green sheet laminates are usually placed in a firing furnace and fired, but depending on the placement location in the firing furnace, there is a possibility that the firing temperature may vary slightly for each laminate. Even if the firing temperature varies slightly in this way, it is preferable to obtain a homogeneous fired body. Therefore, in the composite powder material of this embodiment, the ratio of the density of a sintered body (sintered body (B)) obtained by sintering at 870°C for 60 minutes to the density of a sintered body (sintered body (C)) obtained by sintering at 900°C for 60 minutes, measured by the method described in the Examples section, (a ratio expressed as (density of sintered body (B) / density of sintered body (C))×100) is preferably 101.0% or less, more preferably 100.8% or less, and even more preferably 100.5% or less. Moreover, the percentage is preferably 99.0% or more, more preferably 99.2% or more, and even more preferably 99.5% or more.
[0057] Furthermore, in order to reduce the production cost and to prevent the scale of the facilities from increasing, it is preferable that the firing temperature is lower and the firing time is shorter. Therefore, in the composite powder material of this embodiment, the ratio of the density of the sintered body (sintered body (B)) obtained by sintering at 870°C for 60 minutes to the density of the sintered body (sintered body (A)) obtained by sintering at 870°C for 20 minutes, measured by the method described in the Examples section, (a ratio expressed as (density of sintered body (B) / density of sintered body (A))×100) is preferably 102.0% or less, more preferably 101.5% or less, and even more preferably 101.0% or less. Moreover, the percentage is preferably 98.0% or more, more preferably 98.5% or more, and even more preferably 99.0% or more.
[0058] The composite powder material of this embodiment is preferably sintered by the method described in the Examples section and the dielectric constant at 1 MHz of the sintered body (sintered body (B)) obtained by sintering at 870°C for 60 minutes is measured, and is preferably 6.5 or less, more preferably 6.4 or less, and even more preferably 6.3 or less.
[0059] In this case, the Q value is preferably 500 or more, more preferably 2500 or more, and even more preferably 3300 or more. The significance of the Q value will be explained below. Since the Q value is the reciprocal of the dielectric loss, a large Q value means a low dielectric loss. For various purposes such as narrowing the thickness between layers to make it smaller, narrowing the distance between wiring to make it dense, and improving functionality, the lower the dielectric constant of the material itself is, the more preferable it is. Generally, LTCC green sheets that can be used with silver electrodes are commercially available from Dupont, Ferro, and others. This dielectric constant is about 7 to 8. It is preferable to show a dielectric constant value that is 0.5 or more lower than this dielectric constant, which is significant in design. A Q value of 500 or more is preferable when used in communications as LTCC, since it provides good reception and transmission sensitivity at the relevant frequency and does not consume too much power.
[0060] The composite powder material of this embodiment is sintered by the method described in the Examples section and the dielectric constant of the sintered body (sintered body (C)) obtained by sintering at 900°C for 60 minutes is preferably 6.5 or less, more preferably 6.4 or less, and even more preferably 6.3 or less at 1 MHz. In this case, the Q value is preferably 500 or more, more preferably 2500 or more, and even more preferably 3300 or more.
[0061] The composite powder material of this embodiment is sintered by the method described in the Examples section and the dielectric constant of the sintered body (sintered body (A)) obtained by sintering at 870°C for 20 minutes is preferably 6.5 or less, more preferably 6.4 or less, and even more preferably 6.3 or less at 1 MHz. In this case, the Q value is preferably 500 or more, more preferably 2500 or more, and even more preferably 3300 or more.
[0062] In order to meet the fifth generation communication standard (commonly known as 5G) in communication devices such as mobile phones and smartphones, materials with low dielectric loss, especially in the microwave region, are required. The composite powder material of this embodiment preferably has a dielectric constant of 6.5 or less at high frequencies, more preferably 6.4 or less, even in the case of a sintered body (sintered body (A)) sintered under conditions of a sintering temperature of 870°C and a sintering time of 20 minutes, as measured by the method described in the Examples section. In addition, the Q value in this case is preferably 450 or more, more preferably 470 or more, and most preferably 500 or more. In this specification, a high frequency is equal to or higher than 14 GHz, and it is preferable that the dielectric constant and Q value satisfy the above ranges in the frequency range of 14 GHz to 16 GHz. EXAMPLES
[0063] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.
[0064] [Production of glass composition] Glass raw materials were prepared and mixed to obtain the glass composition shown in Table 1, and melted in a platinum crucible in an electric furnace at 1550°C to 1650°C for 2 hours, and formed into a thin glass sheet to obtain a glass composition. The glass composition was then pulverized in a ball mill to obtain a powder of each glass composition having a D50 of 2.0 μm. Examples 1-1 to 1-4 are working examples, and Examples 1-5 to 1-12 are comparative examples.
[0065] [Evaluation of Glass Composition] The resulting powder of each glass composition was evaluated for shrinkage start temperature Sp and softening point Ts using a differential thermal analyzer. The results are shown in Table 1.
[0066] [Table 1]
[0067] [Manufacturing of composite powder materials] The obtained powder of each glass composition, alumina filler (99.9% purity, corundum single crystal), and magnesia filler (99.9% purity) were mixed in the ratios shown in Table 2, mixed in a wet ball mill using an alcohol solvent for 1 hour, dehydrated, filtered, and dried to obtain each composite powder material. Note that the composite powder material of Example 2-1 uses the powder of the glass composition of Example 1-1, and similarly, the composite powder materials of Examples 2-2 to 2-12 use the powder of the glass compositions of Examples 1-2 to 1-12, respectively. Examples 2-1 to 2-4 are working examples, and Examples 2-5 to 2-12 are comparative examples.
[0068] [Evaluation of composite powder materials] The glass transition temperature Tg, shrinkage onset temperature Sp, and softening point Ts of each of the composite powder materials obtained were evaluated using a differential thermal analyzer. The results are shown in Table 2. In addition, 3 g of the composite powder material was placed in a mold with a diameter of 30 mm, compressed under a pressure of 200 MPa, and sintered at 870°C for 20 minutes, 870°C for 60 minutes, or 900°C for 60 minutes to obtain sintered bodies, which were then measured for density, dielectric constant, and Q value. The measurement methods are as shown below, and the results are shown in Table 2. In Table 2, sintered body (A) refers to the body sintered at 870°C for 20 minutes, sintered body (B) refers to the body sintered at 870°C for 60 minutes, and sintered body (C) refers to the body sintered at 900°C for 60 minutes.
[0069] (Measurement of density) The density of the sintered body obtained by sintering each composite powder material under each sintering condition was measured by Archimedes' method.
[0070] (Measurement of dielectric properties) The dielectric properties were measured using an LCR meter (Agilent, 4192A), by cutting each composite powder material into a cylindrical shape of a given shape (diameter 20 mm, thickness 3 mm), and measuring the dielectric constant and dielectric loss at 20°C and 1 MHz according to the method in accordance with JIS C 2138 (2007). The Q value was calculated as the reciprocal of the dielectric loss.
[0071] (Measurement of dielectric properties at high frequencies) The composite powder materials of Examples 2-1 to 2-4 and 2-12 were sintered at 870°C for 20 minutes to obtain sintered bodies (sintered body (A)), and the dielectric properties at high frequencies were measured. The composite powder materials of Examples 2-1 to 2-4 were sintered at 870°C for 60 minutes to obtain sintered bodies (sintered body (B)) and at 900°C for 60 minutes to obtain sintered bodies (sintered body (C)), which had good dielectric properties at 1 MHz, and the ratio of the density of the sintered body (B) to the density of the sintered body (C) was good. The dielectric properties at high frequencies were measured using a PNA network analyzer N5227A manufactured by Keysight Technologies, Inc., in accordance with the method specified in JIS R 1627 (1996). The measurement frequencies and results are shown in Table 2.
[0072] [Table 2]
[0073] The composite powder materials of Examples 2-1 to 2-4 containing the powders of the glass compositions of Examples 1-1 to 1-4 had a dielectric constant of 6.5 or less at 1 MHz for the sintered body (B) obtained by sintering for 60 minutes at 870°C and a sintered body (C) obtained by sintering for 60 minutes at 900°C, and a Q value of 2500 or more for the sintered body (B) obtained by sintering for 60 minutes at 870°C relative to the density of the sintered body (C) obtained by sintering for 60 minutes at 900°C, both of which were 99% to 101%. From this, it was determined that homogeneous and dense sintered bodies were formed over a wide temperature range. Furthermore, these composite powder materials had a density ratio of 98% to 102% for the sintered body (B) obtained by sintering at 870°C for 60 minutes relative to the density of the sintered body (A) obtained by sintering at 870°C for 20 minutes, and the sintered body (A) obtained by sintering at 870°C for 20 minutes had a dielectric constant of 6.5 or less and a Q value of 500 or more at a high frequency of approximately 15 GHz, indicating that the composite powder materials had excellent dielectric properties. On the other hand, the composite powder materials of Examples 2-5 to 2-12 containing the powder of the glass composition of Examples 1-5 to 1-12 were inferior in at least one of the above-mentioned dielectric constant, Q value, and sinterability. In addition, in the composite powder material of Example 2-12 containing the powder of the glass composition of Example 1-12 not containing an alkali metal oxide, the proportion of the glass composition was increased and the proportion of the alumina filler was reduced, but the ratio of the density of the sintered body (B) obtained by firing at 870 ° C for 60 minutes to the density of the sintered body (A) obtained by firing at 870 ° C for 20 minutes was 104.0%, which was significantly poor, and the sinterability was significantly inferior compared to the Examples. In addition, the Q value at a high frequency of about 15 GHz of the sintered body (A) obtained by firing at 870 ° C for 20 minutes was also significantly inferior at 67.
[0074] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments, and various modifications and substitutions can be made to the above-described embodiments without departing from the scope of the present invention. This application is based on Japanese Patent Application No. 2020-011937 filed on January 28, 2020, the contents of which are incorporated herein by reference.
Claims
1. In terms of oxide mol%, Li 2 O is 0.2% to 1.0%, SiO 2 62% to 67%, B 2 O 3 20% to 29%, CaO 3% to 9%, and Al 2 O 3 3% to 6%; Li 2 O, Na 2 O, and K 2 Molar ratio of the content of O (Li 2 O: Na 2 O:K 2 O) is 1:0-1.9:0-0.
9.
2. 2. The glass composition according to claim 1, excluding those containing ZnO in an amount of 0.5 mol % or more, expressed in mol % on an oxide basis.
3. A ceramic composition comprising Li 2 O and, expressed in mole percent on an oxide basis, 62% to 67% SiO 2 , 20% to 29% B 2 O 3 , 3% to 9% CaO, and 3% to 6% Al 2 O 3 , the molar ratio of the contents of Li 2 O, Na 2 O, and K 2 O (Li 2 O:Na 2 O:K 2 O) is 1:0-1.9:0-0.9; Li 2 O, Na 2 O, and K 2 A glass composition having a total O content of 0.3% to 1.0% expressed in mole percent on an oxide basis.
4. 4. The glass composition according to claim 1, wherein the shrinkage starting temperature is 790° C. or higher.
5. The glass composition according to any one of claims 1 to 4, having a softening point of 900°C or lower.
6. Li 2 4. The glass composition according to claim 3, wherein the O content is 0.2% to 1.0% in mole percent on an oxide basis.
7. A composite powder material containing 45% by mass to 55% by mass of glass powder and 45% by mass to 55% by mass of alumina filler, The glass powder is a powder made of the glass composition according to any one of claims 1 to 6.
8. 8. The composite powder material according to claim 7, having a glass transition temperature of 650°C or higher.
9. 9. The composite powder material according to claim 7 or 8, having a shrinkage start temperature of 820°C or higher.
10. The composite powder material according to any one of claims 7 to 9, having a softening point of 900°C or less.
11. The composite powder material according to any one of claims 7 to 10, wherein when the composite powder material is fired at 870 ° C. for 20 minutes to obtain a fired body (A), and when the composite powder material is fired at 870 ° C. for 60 minutes to obtain a fired body (B), the ratio represented by {density of fired body (B) / density of fired body (A)} x 100 is 98.0% to 102.0%.
12. The composite powder material according to any one of claims 7 to 11, wherein when the composite powder material is fired at 870 ° C. for 60 minutes to obtain a fired body (B), and when the composite powder material is fired at 900 ° C. for 60 minutes to obtain a fired body (C), the ratio represented by {density of fired body (B) / density of fired body (C)} x 100 is 99.0% to 101.0%.
Citation Information
Patent Citations
Low permittivity dielectric ceramic composition for low temperature firing
JP2010006690A
High-strength and high-Q-value dielectric ceramic composition for low-temperature firing
JP2010531287A
Low-temperature firing porcelain composition, low-temperature firing porcelain, and wiring board using the same
JP4047050B2